Kecerdasan Buatan dan Martabat Manusia: Kajian Etis-Teologis-Hermeneutik dalam Konteks Teknologi Modern - Pardede, Nurmalia; Lumban Tobing, Bangun (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2025)
The development of Artificial Intelligence (AI) raises fundamental ethical and theological questions about the nature and dignity of human beings as imago Dei. This phenomenon is important to study because advances in digital technology not only change social and spiritual structures, but also shift human understanding of themselves, their relationships, and their moral responsibilities before God. This study aims to formulate an ethical-theological-hermeneutical framework to understand how AI affects human dignity and how theology can guide its responsible use. This paper uses a literature study method with a theological-philosophical approach and hermeneutical analysis of biblical texts and contemporary literature. The results of the study show that AI tests the limits of classical theological anthropology and demands a redefinition of imago Dei as a relational and moral calling. In conclusion, Christian theology needs to develop a digital ethics model rooted in love, justice, and spiritual responsibility in order to preserve human dignity in the era of autonomous technology. AbstrakPerkembangan Artificial Intelligence (AI) menimbulkan persoalan etis dan teolgis yang mendasar tentang hakikat serta martabat mansuia sebagai imago Dei. Fenomena in penting dikaji karena kemajuan teknologi digital tidak hanya mengubah struktur sosial dan spiritual, tetapi juga menggeser pemahaman manusia tentang diri, relasi, dan tanggung jawab moralnya di hadapan Allah. Penelitian ini bertujuan merumuskan kerangka etis-teologis-hermeneutik untuk memahami bagaimana AI memengaruhi martabat manusia dan bagaimana teologi dapat menuntun pemanfaatanya secara bertanggung jawab. Tulisan ini menggunakan metode studi literatur dengan pendekatan teologis-filofofis dan analisis hermeneutik terhadap tek-teks Alkitab serta literatur kontemporer. Hasil penelitian menunjukkan bahwa AI menguji batas antropologi teologis klasik dan menuntut redefinisi imago Dei sebagai panggilan relasional dan moral. Kesimpulanya, teologi Kristen perlu mengembangkan model etika digital yang berakar pada kasih, keadilan, dan tanggung jawab spiritual guna menjaga martabat manusia di era teknologi otonom.